Adaptive Changes After 2 Weeks of 10-s Sprint Interval Training With Various Recovery Times - Olek, Robert A.; Kujach, Sylwester; Ziemann, Ewa; Ziolkowski, Wieslaw; Waz, Piotr; Laskowski, Radoslaw (Frontiers in Physiology, 2018)
Purpose: The aim of this study was to compare the effect of applying two different rest recovery times in a 10-s sprint interval training session on aerobic and anaerobic capacities as well as skeletal muscle enzymes activities. Methods: Fourteen physically active but not highly trained male subjects (mean maximal oxygen uptake 50.5 ± 1.0 mlO2•kg-1•min-1) participated in the study. The training protocol involved a series of 10-s sprints separated by either 1-min (SIT10:1) or 4-min (SIT10:4) of recovery. The number of sprints progressed from four to six over six sessions separated by 1-2 days rest. Pre and post intervention anthropometric measurements, assessment of aerobic, anaerobic capacity and muscle biopsy were performed. In the muscle samples maximal activities of citrate synthase (CS), 3-hydroxyacylCoA dehydrogenase (HADH), carnitine palmitoyl-transferase (CPT), malate dehydrogenase (MDH) and its mitochondrial form (mMDH), as well as lactate dehydrogenase (LDH) were determined. Analysis of variance was performed to determine changes between conditions. Results: Maximal oxygen uptake improved significantly in both training groups, by 13.6% in SIT10:1 and 11.9% in SIT10:4, with no difference between groups. Wingate anaerobic test results indicated main effect of time for total work, peak power output and mean power output, which increased significantly and similarly in both groups. Significant differences between training groups were observed for end power output, which increased by 10.8% in SIT10:1, but remained unchanged in SIT10:4. Both training protocols induced similar increase in CS activity (main effect of time p<0.05), but no other enzymes. Conclusion: Sprint interval training protocols induce metabolic adaptation over short period of time, and the reduced recovery between bouts may attenuate fatigue during maximal exercise.